Keragaan Karakter Kuantitatif Cabai Hibrida IPB di Dataran Rendah Karawang - Sianturi, Clarissa Yolanda; Syafi’i, Muhammad; Syukur, Muhamad (JURNAL AGROPLASMA, 2023)
Chili (Capsicum annuum L.) is a horticultural commodity that has high economic value and is widely used for both household and industrial needs. This study aims to identify the quantitative characters of IPB chili varieties in the Karawang Lowlands that have the best potential in the Karawang Lowlands.This research was conducted from April 2022 to August 2022 at the Lahan Percobaan PERURI in Teluk Jambe Timur, Karawang Regency, West Java. This study was arranged using a Ramdomized Group Design (RGD) with 10 genotype treatments and 3 replications, in each land there were 10 samples with a total of 300 experimental units. The data were analyzed using analysis of variance and DMRT (Duncan Multiple Range Test) at 5% level. The results of this experiment indicated that there was a significant effect of the quantitative character appearance of red chili on the components of flowering age, harvesting age, plant height, fruit weight, fruit diameter, fruit weight, 1000 seed weight, number of each fruit plant, weight of each land, productivity. The G1, G2, and G3 genotypes have the potential to be listed as new varieties because they have better yielding power that is different from the genotypes of other commercial varieties..Keywords: hybrid, character, performance, productivity, superior varieties